Estimated Economic Growth Rate Based on Efek Decrease in PPKM Level Using Support Vector Regression Method - Daniel Setyo Cahyo Utomo; Adi Nugroho (Universitas Bina Darma, 2022)
Economic growth is a change in economic conditions towards a better level. An increase in the value of income and production will affect the condition of a country. It can be known that the impact of Covid-19 is enough to affect economic conditions in Indonesia. Economic conditions in Indonesia are also affected by the PPKM program from the government. The bill of decreasing the PPKM level that is applied is considered to provide an increase in the economy towards normal and better. The purpose of this study is to provide predictions and analysis of the value of future economic growth. The method used is SVR (Support Vector Regression). This method is processed using a Polynomial kernel and using MAPE (Mean Absolute Percentage Error) error accuracy. Based on research that has been carried out, the results of the value of each economic nit in the fourth quarter of 2021 and the first to fourth quarters of 2022 with a MAPE value of 3.6% which is included in the very good category. In this study, an analysis was also obtained that there will be an economic increase of 1.14% along with a decrease in the PPKM level.